Designing A User Interface and User Experience from Piring Makanku Application by Using Figma Application for Teens - ZE. Ferdi Fauzan Putra; Hamidillah Ajie; Ika Anwar Safitri (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
This study is aimed to design a user interface for Piring Makanku application that can be used for a promotion medium to introduce Piring Makanku program issued by the Ministry of Health, for the teens aged 15-18. A Figma webapp was employed as a tool for designing this interface quickly and easily. Whereas A Lean UX method, which is one method in designing UX, was used to design the interface shortly and effectively. A usability test with Retrospective Thinking Aloud was applied to measure whether or not the design can be accepted by the teen users. Findings derived from the stages of the test revealed that the design can be accepted by teens with positive response of 95.56% out of the total 5 respondents. It can be concluded that the interface to have been designed becomes appropriate for development into Piring Makanku application layout.